2013
DOI: 10.15288/jsad.2013.74.909
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Initiation During College Predicts Future Alcohol Involvement: A Matched-Samples Study

Abstract: ABSTRACT. Objective:Little is known about the relationship between cigarette smoking initiation and subsequent alcohol involvement. To address this question, the present study compared alcohol use between students who initiated smoking during college and a matched sample of never-smoking students. We hypothesized greater increases in alcohol involvement among smoking initiators, mediated by exposure to cigarette use situations. Method: Included in the present study were 104 Chinese American and Korean American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…These results are aligned with the evidence where students who smoke appear to be at an increased risk for drinking and alcohol involvement (e.g. binge-drinking behaviours) (Harrison, Hinson, & McKee, 2009;Myers, Doran, Edland, Schweizer, & Wall, 2013) and smoke more during drinking episodes (Witkiewitz et al, 2012). Moreover, the consumption of tobacco and/or alcohol may be associated with illicit substances use (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…These results are aligned with the evidence where students who smoke appear to be at an increased risk for drinking and alcohol involvement (e.g. binge-drinking behaviours) (Harrison, Hinson, & McKee, 2009;Myers, Doran, Edland, Schweizer, & Wall, 2013) and smoke more during drinking episodes (Witkiewitz et al, 2012). Moreover, the consumption of tobacco and/or alcohol may be associated with illicit substances use (e.g.…”
Section: Discussionsupporting
confidence: 84%
“…Such experiences lead to the excessive consumption of alcohol, which may be considered as normal cultural behaviour. Furthermore, the use of alcohol may be related to issues of low self-esteem, professional and/or personal problems and peer pressure (26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the observed relations between cannabis involvement with tobacco/alcohol consumption and type A polydrug behaviours, the evidence showed that these consumptions are not independent with the reference group (Hernández-Serrano, Font-Mayolas, & Gras, 2015) and part of the substance's involvement could be explained by environmental factors, specially the exposure to situations where consumption is present (Myers, Doran, Edland, Schweizer, & Wall, 2013). For instance, one study showed that heavy drinking can occur when cannabis is used (Metrik, Gunn, Jackson, Sokolovsky, & Borsari, 2018) and smoker students present higher levels of alcohol use (McKee et al, 2004).…”
Section: Discussionmentioning
confidence: 90%